DAYA TARIK DAN POTENSI DAYA TARIK KAWASAN CANDI SELOGRIYO - Sugiarto, Eko (Kepariwisataan: Jurnal Ilmiah, 2017)
This research aims at exploring tourist attraction and the potentials of Selogriyo Temple and its area in Magelang District. The method used is qualitative method. The types of data are primary data and secondary data. The primary data are obtained from observation and interview. The secondary data are obtained from literature review or relevant various literature study and then the results are used as the supporting data for the primary data. The results of this research show that the attraction of Selogriyo Temple and its area located in rice field terracing, local residents activity, and art show. Besides, there are some objects which are potential to be tourist attraction (the temple, sunrise panorama, and settlement in Campurejo Village). Keywords: attraction, potential, region